Does increasing maximal strength improve sprint running performance? - Cronin, J.; Ogden, T.; Lawton, T.; Brughelli, M. (Strength and Conditioning Journal, 2007)
A strength base is considered critical to speed development and, consequently, a great deal of effort is spent improving the force capability of muscle. Using a correlational approach is one method used to quantify the relationship between strength and speed. However, better insight may be found investigating longitudinal studies that have quantified both strength and speed changes. Such an approach was used in this review to determine the magnitude of strength development necessary for improved running speed.